The Necessity of a Paradigm Shift in Korean Welfare Policy and Tasks to Be Pursued - Heesuk Yun (Korea Development Institute (KDI), 2014)
If 'welfare through work' is to become a reality, Korea should dispense with the old method of haphazardly importing welfare programs based on one-to-one comparisons with developed countries and instead redefine the overarching goal of the welfare system by establishing a universal structure that supports employment and mobility and aligns various welfare programs as components of that system. - Linking work and welfare does not merely mean connecting existing welfare programs with programs that help people find jobs. Rather, it means modifying existing welfare programs or considering the option of introducing new programs under the primary goal of "welfare through work". - The rapidly changing global economy strengthens the need for a paradigm shift in the welfare system. Korea should move away from protecting income and jobs and toward empowering people to stay employed as they transition from one job to another. - The overarching goal of welfare through work conflicts with certain individual programs that have been brought to Korea without taking account of the actual situation in the country. One such program is the family care allowance program. This program, which decreases the incentive for women to find work, has been expanded despite the fact that the Korean employment ratio for women with infants and young children is hovering around 30–40%. - Two different government agencies are handling housing assistance, and they have expanded this assistance without coordinating their efforts. It remains unclear what overarching goal can be used to harmonize them. - The most vulnerable group is households in which no one is employed. With less than 1% of workers at small companies (those with less than five employees) enrolled in labor unions, social policy debate has become inflexible as the focus remains on unions. There is a need for the government to assume a greater role in directing social policy.
Keywords: 330